2023
DOI: 10.1111/padm.12962
|View full text |Cite
|
Sign up to set email alerts
|

Paths to trust: Explaining citizens' trust to experts and evidence‐informed policymaking during the COVID‐19 pandemic

Angelos Angelou,
Stella Ladi,
Dimitra Panagiotatou
et al.

Abstract: The COVID‐19 pandemic brought forward new questions about the efficient implementation of arduous public policies. Drawing evidence from the pandemic, this article argues that, during crises, policymakers will often opt for evidence‐informed policymaking, hoping for better results. In line with previous studies, we show that citizens trust more policies coming from experts rather than policymakers and elected politicians. We also add nuance to these claims as we attribute this tendency to the technocratic legi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…First, the electoral processes of post-communist countries compared to those in Eastern European countries are characterised by more divergent historical, political, and societal contexts which might affect the citizens' political behaviour. Therefore, in post-communist countries, the challenges of conducting elections during the pandemic were compounded by preexisting vulnerabilities in democratic institutions, varying levels of public trust in government, and often more contentious political environments (Merkel and Lührmann, 2021), while in Western countries the level of public trust is higher and the democratic process is more consolidated, enabling them to navigate the pandemic's challenges with less controversy (Angelou et al, 2023;Boin et al, 2021). However, the literature highlights the ongoing struggle of both Western and Eastern countries to balance public health priorities with the imperative of democratic participation (Burkle, 2020;Hosseini, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, the electoral processes of post-communist countries compared to those in Eastern European countries are characterised by more divergent historical, political, and societal contexts which might affect the citizens' political behaviour. Therefore, in post-communist countries, the challenges of conducting elections during the pandemic were compounded by preexisting vulnerabilities in democratic institutions, varying levels of public trust in government, and often more contentious political environments (Merkel and Lührmann, 2021), while in Western countries the level of public trust is higher and the democratic process is more consolidated, enabling them to navigate the pandemic's challenges with less controversy (Angelou et al, 2023;Boin et al, 2021). However, the literature highlights the ongoing struggle of both Western and Eastern countries to balance public health priorities with the imperative of democratic participation (Burkle, 2020;Hosseini, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is all the more remarkable after acknowledging that public participation is repeatedly recommended in health disaster response literature" (Mouter, Hernandez, and Itten 2020) [p. 3] However, another corpus of 18 studies was identified that collected POD regarding COVID policy but did not explicitly use this data to inform COVID policymaking. (Angelou et al 2023;Behal, Davis, and Doering 2023;Fatihin et al 2022;Fitriansyah et al 2021;Hu et al 2021;Ifdil et al 2023;Kemper et al 2023;Kobayashi et al 2022;Loría-Rebolledo et al 2022;McCormick et al 2023;Morita et al 2023;Ntale and Ngoma 2021;Shakeel et al 2023;Sukhwal and Kankanhalli 2022;Suratnoaji, Nurhadi, and Arianto 2020;Veldwijk et al 2023;Yanuar Fahmi Pamungkas et al 2021;Yigitcanlar et al 2020) We therefore present commentary in two parts -first, analysis of the three studies meeting the review inclusion criteria; second, analysis of the 18 studies not explicitly connecting POD to policymaking. The rationale for including analysis of these 18 studies is to provide further practical insights on methods of POD data collection, given that very little research explicitly examined the influence of POD on public policymaking.…”
Section: "Government Driven Public Participation In Covid-19 Policyma...mentioning
confidence: 99%
“…The POD collected across the included studies encompassed key COVID-19 policy decision-making challenges encountered in numerous jurisdictions across the world including vaccines (Behal 2023, Hu 2021, Kobayashi 2022, Yanuar Fahmi Pamungkas 2021, COVID-19 certificates, lockdowns (Loria-Rebolledo 2022) and travel behaviours. In addition to providing perspectives on policy options, some studies focused on other topics including public perspectives on the role of public engagement (Kemper 2023) and experts (Angelou 2023) in COVID-19 policymaking; evaluation of education and awareness-raising efforts; (Fatihin 2022) and how businesses and households adapted to the pandemic. (Fitriansyah 2021) These studies broadly supported the findings of the three included studies regarding feasibility and / or usefulness of both social media analytics (Sukhwal 2022, Suratnoaji 2020, Yigitcanlar 2020) and survey-based methodologies (Behal 2023).…”
Section: Analysis Of Included Studies (N = 3)mentioning
confidence: 99%